(untitled) (Research, Society and Development, 2021)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder with undefined etiology and varying degrees of severity. It is characterized by deficits in communication and social interaction, and restrictive behavior patterns. The dental care of these patients is challenging, because their clinical manifestations are complex and varied. This occurs because the dental environment, and the service itself, have potential triggers for behavioral changes in people with ASD, since they have a greater sensitivity to the stimuli present in the dental office. This study is a literature review that aims to identify the behavioral management strategies employed by the dentist when facing the challenges faced by the autistic patient. A bibliographic survey of articles indexed in the electronic databases PUBMED, SCIELO, and BVS was carried out using the descriptors "autism spectrum disorder", "autism", "oral health", "behavior", and "dental care". Articles from the last 10 years were selected in their entirety, excluding those that were not well grounded on the theme. The dental management of the patient with ASD requires individualization and understanding of his behavior, encompassing different techniques such as: tell- show-do, short sessions, elimination of stressful sensory stimuli, voice control, modeling, in addition to the educational approaches PECS, ABA and TEACCH. It is concluded that, despite the challenges, quality dental treatment can be accomplished with the use of personalized approaches, for this, it is necessary that the dental surgeon knows these resources and master the technique.